Classification of Multifractal Time Series by Decision Tree Methods - Булах, В. А.; Кіріченко, Л. О.; Радівілова, Т. А. (КНУ, 2018)
The article considers classification task of model fractal time series by the methods of machine learning. To classify the series, it is proposed to use the meta algorithms based on decision trees. To modeling the fractal time series, binomial stochastic cascade processes are used. Classification of time series by the ensembles of decision trees models is carried out. The analysis indicates that the best results are obtained by the methods of bagging and random forest which use regression trees.
Keywords: multifractal time series; binomial stochastic cascade; classification of time series; Random Forest; Bagging